2002
DOI: 10.1176/appi.ajp.159.10.1696
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep and the Early Development of Posttraumatic Stress Disorder

Abstract: The development of PTSD symptoms after traumatic injury is associated with a more fragmented pattern of REM sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
280
4
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 365 publications
(305 citation statements)
references
References 37 publications
19
280
4
2
Order By: Relevance
“…However, REM sleep architecture appeared non-disrupted in individuals with chronic PTSD [42]. These findings are consistent with previous literature in treatment-seeking, non-minority [43], and military populations [44]. Trauma-exposed individuals without PTSD, compared to those with PTSD, exhibit elevated right frontal theta power (4-8 Hz) during REM sleep.…”
Section: Rdoc Framework-based Correlates Of Trauma and Sleepsupporting
confidence: 89%
“…However, REM sleep architecture appeared non-disrupted in individuals with chronic PTSD [42]. These findings are consistent with previous literature in treatment-seeking, non-minority [43], and military populations [44]. Trauma-exposed individuals without PTSD, compared to those with PTSD, exhibit elevated right frontal theta power (4-8 Hz) during REM sleep.…”
Section: Rdoc Framework-based Correlates Of Trauma and Sleepsupporting
confidence: 89%
“…Although the present study focused on insomnia, the role of restless REM sleep in emotion regulation appears highly relevant to other realms of psychiatry. Restless REM sleep is present in MDD (18) and PTSD (19,20). Importantly, insomnia impedes the effectiveness of depression intervention (4), whereas treatment of insomnia improves remission from MDD (3).…”
Section: Discussionmentioning
confidence: 99%
“…We use the term "restless REM sleep" here to refer to REM sleep with a high number of phasic events, including arousals and eye movements. These phasic events commonly occur not only in insomnia (5) but also in depression (18) and posttraumatic stress disorder (PTSD) (19,20). If restless REM sleep interferes with the overnight resolution of emotional distress, it could contribute to its accumulation, appearing as a chronically hyperaroused state.…”
mentioning
confidence: 99%
“…An early report of 3 cases with "acute combat fatigue" described "markedly disrupted sleep" and "rare or absent rapid eye movement (REM) episodes" (51). Mellman et al (52) reported PSG findings from PSG recordings conducted within a month of trauma in 21 recently injured patients and 10 healthy controls. REM eye movement density was elevated in the recently trauma exposed, injured patients compared with healthy controls but were similar among those who did and did not develop PTSD.…”
Section: Sleep In Posttraumatic Stress Disordermentioning
confidence: 99%